The Category of Number in Dıfferent Language Systems - BAYRAMOVA, AYTEN MAHAMMAD (Advances in Social Sciences Research Journal, 2017)
Philosophical or logical category of number is based on the existence of quantitative characteristics of things and events of the reality. A human being first comprehended the number of things and objects and then tried to express them by means of languages. Gradually there appeared the existence of more than one things and there emerged the necessity of expressing them. In Turkic languages, including Azerbaijani, the abundance of things began to be expressed by the numeral three, then it reached forty, which was the maximal limit. It found its expression in fairy-tales and eposes, as well as in proverbs. For instance: Atalar üçəcən deyiblər (Our forefathers counted up to theree or allowed do something only thrice); Üç gün, üç gecə yol getdilər (They walked three days and nights); Qırx gün möhlət vermək(They granted him a delay for forty days); Qırx gün, qırx gecə döyüşmək (They fought for forty days and nights); qırx qapını açmaq (to open forty doors); divin canını qırxıncı otaqda tapmaq (to find the vigour (life) of the giant in the fortieth room), etc. All this shows that the expression of the category of number in language has undergone a long historical process.